Studi Komparasi Penggunaan Metode Ceramah dan Metode Mind Map Terhadap Hasil Belajar IPA pada Siswa Kelas V SD Muhammadiyah 10 Tipes Surakata Tahun Ajaran 2015/2016 - YUNIASTUTI, WIWIN (2016)
This study aims to determine whether the strategy Modeling the Way with media images can improve speaking skills in learning Indonesian in class V SDN 3 Candisari year 2015/2016. The subjects of research that fifth grade teachers and students of class V SDN 3 Candisari number of 22 students. This research is a class act. The experiment was conducted during two cycles or four meetings. Collecting data through interviews, observation, and documentation. As for the validity of the source data using triangulation and triangulation of data collection techniques. The results showed an increase conversational skills, namely: 1) the pre-stage cycle of 36.36%, 2) At the stage of the first meeting of the first cycle increased to 45.45%, 3) the second meeting increased to 59.09%, 4) on The first meeting of the second cycle increased to 72.27%, 5) the second meeting increased to 90.91%. The conclusion of this study is the strategy Modeling the Way with media images can improve speaking skills in class V SDN 3 Candisari year 2015/2016.